How does visual attention differ between experts and novices on physics problems? - Carmichael, Adrian; Larson, Adam; Gire, Elizabeth; Loschky, Lester C.; Rebello, N. Sanjay (My University, 2011)
Eye movement data has been shown to enhance our understanding of student's problem solving behaviors in physics and also help us identify differences between novices and experts. In this study we compare the eye movement data of experts and novices using introductory conceptual physics problems. The problems chosen all utilize concepts that have an inherent spatial component in their visual representation. To become aware of the critical concept in each problem, the solver must attend to that spatial component of the figure. To gain additional information about how the experts and novices answered each problem, we interviewed the participants about the reasoning process they used and compared these answers to the eye movements. We will discuss our results from interviews as well as eye-tracking data from both experts and novices.
Keywords: Physics education; Problem solving; Graphs; Visual attention; Eye movements; Fixations; Expertise; Experts; Novices